Characterisation metrics for performance comparison of area scan and event-based sensors - Manakov, Alkhazur; Herrmann, Helmut; Jähne, Bernd (Technisches Messen, 2025)
This paper provides a methodology to directly compare the performance of event-based and traditional area scan cameras. Event-based cameras offer high temporal resolution, wide dynamic range (120dB), low power consumption, and a compressed output stream, making them attractive for robotics and computer vision in challenging environments. However, the lack of a standardized comparison method between the two types of sensors has made it difficult to evaluate their relative performance and decide which camera is more suitable for which application. Here, we show that a set of three performance parameters, namely event contrast detectability (ECD), latency or maximum event rate, and event detection efficiency (EDE), can be used to quantitatively compare the performance of area scan and event-based cameras. The theoretical investigations are verified by a comparison study with 3 event-based and 3 industry standard area scan sensors, including a high dynamic range SONY IMX490 sensor to match the dynamic range of event-based cameras. For this purpose, the dynamic range of the EMVA 1288 compliant test equipment was extended to 120dB.